Human Growth Hormone Delivery with a Microneedle Transdermal System: Preclinical Formulation, Stability, Delivery and PK of Therapeutically Relevant Doses - Mahmoud Ameri; Miryam Kadkhodayan; Joe Nguyen; Joseph A. Bravo; Rebeca Su; Kenneth Chan; Ahmad Samiee; Peter E. Daddona (MDPI AG, 2014)
This study evaluated the feasibility of coating formulated recombinant human growth hormone (rhGH) on a titanium microneedle transdermal delivery system, Zosano Pharma (ZP)-hGH, and assessed preclinical patch delivery performance. Formulation rheology and surface activity were assessed by viscometry and contact angle measurement. rhGH liquid formulation was coated onto titanium microneedles by dip-coating and drying. The stability of coated rhGH was determined by size exclusion chromatography-high performance liquid chromatography (SEC-HPLC). Preclinical delivery and pharmacokinetic studies were conducted in female hairless guinea pigs (HGP) using rhGH coated microneedle patches at 0.5 and 1 mg doses and compared to Norditropin® a commercially approved rhGH subcutaneous injection. Studies demonstrated successful rhGH formulation development and coating on microneedle arrays. The ZP-hGH patches remained stable at 40 °C for six months with no significant change in % aggregates. Pharmacokinetic studies showed that the rhGH-coated microneedle patches, delivered with high efficiency and the doses delivered indicated linearity with average Tmax of 30 min. The absolute bioavailability of the microneedle rhGH patches was similar to subcutaneous Norditropin® injections. These results suggest that ZP-transdermal microneedle patch delivery of rhGH is feasible and may offer an effective and patient-friendly alternative to currently marketed rhGH injectables.